Conquista y Colonización en América: un estudio comparado entre España e Inglaterra, Siglos XVI y XVII - Redi, Cristian (European Scientific Journal, ESJ, 2017)
This is a comparative study between Spanish and English colonization in American lands, the period in question covers the sixteenth and seventeenth centuries characterized by a bitter rivalry between the two powers. These historical processes were decisive in the later development of the occupied zones, modifying both the social structures as well as the geographical spaces. We understand that there existed in both monarchies a particular spirit that guided their actions. Especially in relation to individual activity, repressed by the Spaniards and fomented by the English, they gave their colonies certain characteristics that are analyzed in the present work.